A Pelatihan Calon Kader Posbindu Remaja Tentang Pencegahan Penyakit Tidak Menular Di Dusun Kembaran Kecamatan Kasihan Kabupaten Bantul - Anggoro Prakoso, Denny; Nurul Hidayah, Fitria (J-Dinamika : Jurnal Pengabdian Masyarakat, 2023)
Diabetes and hypertension are non-communicable diseases that have a high prevalence worldwide and have a significant impact on public health. This disease is increasingly common in adolescents and if left unchecked can seriously impact their health . Both have a close relationship with unhealthy lifestyles such as unhealthy diets, lack of physical activity, and obesity. Therefore, it is imperative to increase awareness and education in adolescents. Prevention and management of diabetes and hypertension in adolescents must be a top priority in maintaining public health. The purpose of this community service is to increase adolescent knowledge about the prevention and management of the risk of diabetes and hypertension. The method used is health education with counselling, electronic modules and discussions with experts. Besides that, to see an increase in adolescent knowledge, pre-tests and post-tests are carried out and the results are analyzed by independent t-test. Evaluation of the activity resulted in a significant increase in adolescent knowledge in the aspects of prevention and risk management of diabetes and hypertension. The conclusions of the results of community service, health education with counselling, electronic modules and discussions are effective in helping increase adolescent knowledge about the prevention and management of diabetes and hypertension.